Drummond : a origem de um enigma - Sachett, Gabriel Costa (My University, 2014)
This work discusses the constitution of the being in time and in space throughout the work Claro enigma, by Carlos Drummond de Andrade. Therefore, it uses theoretical principles from philosophy, history, sociology, economy, in order to comprehend the diverse dimensions in which the Being shows himself. It examines the general aspects of the individual’s social formation, in the course of the Brazilian history, as well as the specific aspects of the author, considering the psychological and philosophical dimension of his work. It’s, so, an interdisciplinary discussion that mingles the author’s life and work with the Brazilian history and its peculiarities.
Este trabalho discute a constituição do Ser no tempo e no espaço, a partir da obra Claro enigma, de Carlos Drummond de Andrade. Para tanto, são utilizados fundamentos filosóficos, históricos, sociológicos, econômicos, no intuito de abranger as diversas dimensões em que o Eu se revela. Examinam-se aspectos gerais da formação social dos indivíduos, ao longo da história brasileira, bem como aspectos específicos do autor, tendo por base a dimensão psicológica e filosófica de sua obra. Trata-se, portanto, de uma discussão interdisciplinar que relaciona vida e obra do autor à história do Brasil e suas peculiaridades.
Keywords: Andrade, Carlos Drummond de; Claro Enigma (Obra literária); Poesia brasileira; Crítica